Pengaruh Pertumbuhan Penjualan, Umur Perusahaan dan Risiko Bisnis terhadap Struktur Modal pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Rena Yuliana Nur Aini (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
This study aims to determine the influence of sales growth, company age, and business risk on the capital structure of property and real estate companies listed on the Indonesia Stock Exchange from 2020-2023. This research uses a quantitative approach with descriptive statistical methods. The population in this study consists of property and real estate companies listed on the Indonesia Stock Exchange from 2020-2023. The sample was selected using purposive sampling, resulting in 28 financial report data samples. The study used SPSS version 25 for analysis. The findings indicate that sales growth does not affect the capital structure, company age affects the capital structure, business risk does not affect the capital structure, and simultaneously, sales growth, company age, and business risk do not affect the capital structure.